(untitled) (The Pretoria Student Law Review, 2021)
This article reflects on the fallacy of post-apartheid jurisprudence (particularly, the Marikana Massacre as a cornerstone of this ‘fallacy’) in South Africa. For the purposes of this article, the term ‘fallacy’ is used in its literal sense – that is, the so-called ‘post-apartheid jurisprudence’ is a mistaken belief, because there is still residue of apartheid economic policies in the ‘post’-apartheid legal dispensation. This mistaken belief is demonstrated below considering the events that took place prior (i.e. economic policies), during (i.e. law from below) and after (i.e. access to Justice) the Marikana Massacre, and how one of the instrumental projects of post-apartheid legal dispensation, that of transformative constitutionalism, was hindered during these events.